PENGARUH TEACHING GAME FOR UNDERSTANDING (TGFU) TERHADAP HASIL BELAJAR PERMAINAN SEPAK BOLA (STUDI DALAM KONTEKS SEKOLAH DASAR) - Adhi Virama, La Ode; Karim, Karim; Dalman, Dalman (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2023)
The aim of this research is to find out whether the numbered head together learning model has a significant influence on students' learning outcomes in the game of soccer in elementary schools. This model uses quantitative research methods, this research was conducted in elementary schools with a sample of 16 class VI students. Data collection was carried out using observation instruments, tests and documentation. This research measures the effect of the TGFU model and modified ball on increasing students' active learning time as a result of playing soccer. The instrument used is The Game Performance Assessment Instrument (GPAI). To obtain data on the results of learning about soccer skills, The Game Performance Assessment Instrument was used. The Game Performance Assessment Instrument (GPAI) can be used as a means to assess the ability to play games in sports. The results of this research show that there is a significant influence between Teaching Game For Understanding on the learning outcomes of elementary school students in the game of soccer with a calculated t value of 2.631 with a significant value (sig) of 0.014 < 0.05, which means the variable X (Teaching Game For Understanding) on the terical variable (soccer game learning outcomes) is 19.8%.